Foreign Aid and Fiscal Behavior in a Bounded Rathionality Model: Different Policy Regimes - Ira N. Gang; Haider Ali Khan (Rutgers University, Department of Economics, 1998)
We examine how the source of foreign aid affects the composition of the recipient government's spending. Does the source of aid – bilateral or miltilateral – influence ricipient policy-makers' choice between development and nondevelopment expenditure? We depart from previous literature by introducing strong asymmetries in policy-maker's preferences. With financial constraints set by foreign aid and domestic revenues, this formalization allows us to model and estimate the fiscal behavior of government policy-makers in the presense of foreign aid.
Keywords: F35; 330; foreign aid; India; international assistance